Subcellular Evidence for Biogenesis of Autophagosomal Membrane during Spermiogenesis In vivo - Huang, Yufei; Yang, Ping; Liu, Tengfei; Chen, Hong; Chu, Xiaoya; Ahmad, Nisar; Zhang, Qian; Li, Quanfu; Hu, Lisi; Liu, Yi; Chen, Qiusheng (Frontiers in Physiology, 2016)
Although autophagosome formation has attracted substantial attention, the origin and the source of the autophagosomal membrane remains unresolved. The present study was designed to investigate in vivo subcellular evidence for the biogenesis of autophagosomal membrane during spermiogenesis using transmission-electron microscopy (TEM), Western blots and immunohistochemistry in samples from the Chinese soft-shelled turtle. The testis expressed LC3-II protein, which was located within spermatids at different stages of differentiation and indicated active autophagy. TEM showed that numerous autophagosomes were developed inside spermatids. Many endoplasmic reticulum (ER) were transferred into a special “Chrysanthemum flower centre” (CFC) in which several double-layer isolation membranes (IM) were formed and extended. The elongated IM always engulfed some cytoplasm and various structures. Narrow tubules connected the ends of multiple ER and the CFC. The CFC was more developed in spermatids with compact nuclei than in spermatids with granular nuclei. An IM could also be transformed from a single ER. Sometimes an IM extended from a trans-Golgi network and wrapped different structures. The plasma membrane of the spermatid invaginated to form vesicles that were distributed among various endosomes around the CFC during spermiogenesis. All this cellular evidence suggests that, in vivo, IM was developed mainly by CFC produced from ER within differentiating spermatids during spermiogenesis. Vesicles from Golgi complexes, plasma membranes and endosomes might also be the sources of the autophagosome membrane.